ICM based ANFIS MPPT controller for grid connected photovoltaic system - Pavan Kumar Naidu, R; Meikandasivam, S (International Journal of Engineering and Technology, 2018)
In this paper, grid-connected photovoltaic (PV) system is presented. PV system consists of a photovoltaic module, a boost converter, and voltage source inverter. ANFIS based ICM (Incremental Conductance Method) MPPT (Maximum Power Point Tracking) controller is utilized to produce gate signal for DC-DC boost converter. This controller is used for optimizing the total performance of the Photovoltaic system in turn the errors were reduced in Voltage Source Inverter (VSI). The grid-connected PV system performance is evaluated and har-monics occurred in the system are decreased. The proposed methodology is implemented in MATLAB/Simulink.Â